Political Branding Strategy Of Rano Karno Through The Tiktok Account @H.Ranokarno During The 2024 Jakarta Regional Election - Muhammad Fatih Al Kautsar; Muhammad Prakoso Aji (UNIVERSITAS PAKUAN, 2026)
Political branding has become an increasingly important strategy in digital political communication, particularly on algorithm-driven social media platforms such as TikTok. This study aims to analyze the political branding strategy employed by Rano Karno through the TikTok account @h.ranokarno during the 2024 Jakarta Regional Election campaign. A qualitative approach with a netnographic method was adopted. Primary data were collected through in-depth interviews with five key informants and digital observation of campaign content, while audience responses were examined through the analysis of 1,563 TikTok comments using RapidMiner. The analysis was guided by the Political Branding framework proposed by Pich and Newman (2021), encompassing the dimensions of tangible, intangible, brand trinity, and symbolic communication and trust. The findings reveal that Rano Karno's long-established